Effect of fiber source on performance of weanling pigs - Thulin, A.J.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ninety-six Yorkshire pigs, weaned at 5 to 6 weeks of age and averaging 9.5 kg (20.9 lbs.) were used to determine the effects of diets with increased fiber from oats, beet pulp, wheat bran, alfalfa meal or wheat shorts on performance and fecal consistency. Pigs fed the control, 20% oats, 10% beet pulp or 21.2% wheat bran diets had the best average daily gain; those fed the 48.5% wheat shorts, the poorest daily gain. Average daily feed intake was similar except that pigs fed the 20% oats diet consumed more feed (P<.05) than those fed the 48.5% wheat shorts. Feed efficiency was similar for all diets. Pigs fed the control, 20% oats, 10% beet pulp or 21.2% wheat bran diets had better average daily diarrhea scores than those fed the 7.6% alfalfa meal or 48.5% wheat shorts diets.
Keywords: Swine; Fiber source; Performance; Weanling pigs